Conflict of Interest under Article 8(5) of the Indonesian Prosecution Service Law: An Analysis of Central Jakarta District Court Decision No. 38/Pid.Sus-TPK/2020/PN Jkt.Pst - Arif Hadi Ramadhana; EMK Alidar; Riza Afrian Mustaqim (Fakultas Syariah IAIN Langsa, 2026)
Ideally, Article 8 paragraph (5) of the Law on the Indonesian Prosecution Service should function as a preventive legal instrument to safeguard prosecutorial independence by preventing conflicts of interest, thereby ensuring that criminal proceedings are conducted objectively, impartially, and in accordance with the principles of due process of law. In practice, however, the prosecution of the Pinangki Sirna Malasari case reveals that the provision lacks clear operational standards, raising concerns regarding the effectiveness of conflict-of-interest regulation in cases involving prosecutors themselves. This study aims to examine the implementation of Article 8 paragraph (5) of the Law on the Indonesian Prosecution Service through the decision of the Central Jakarta District Court Number 38/Pid.Sus-TPK/2020/PN Jkt.Pst and to assess its implications for prosecutorial independence and the fairness of criminal proceedings. This research employs a normative legal method with a qualitative approach, using statute, case, and conceptual approaches. The findings indicate that the implementation of Article 8 paragraph (5) remains largely declaratory, as it is not supported by effective mechanisms for conflict-of-interest disclosure, recusal, or independent oversight. Strengthening the regulatory framework is essential to reinforce prosecutorial independence, enhance institutional accountability, and ensure a fair and credible criminal justice process.